Comparative analysis of exoproteome staphylococcus aureus isolated from asymptomatic carrier and different infection types - Liew, Yun Khoon (2013)
Staphylococcus aureus (S. aureus) is a highly versatile pathogen that can survive under diverse in vitro and in vivo environmental conditions. The success of S. aureus is mainly driven by the extracellular proteins (exoproteins). Understanding the exoproteome of S. aureus isolates from different host and clinical manifestations as well as the host humoral and inflammatory responses is important in identifying potential virulence and diagnostic markers, and vaccine candidates. Firstly, silver staining technique was optimized prior to proteomic study to obtain a clear resolution of proteome. The modified silver staining helped to visualize the lower molecular mass and low abundant protein spots. Besides that, enhancedresolution images of co-migrating spots with variable abundance intensities were also achieved. The modified silver staining allowed the detection of proteins loaded at extremely low concentrations, ranging from 0.0048 to 0.0480 μg/μL. Therefore, all further investigations were carried out with modified silver staining method. Analysis of the exoproteome of pig-associated S. aureus strain (sequence type 9 (ST9)) isolated from human and pig showed similar protein patterns, however variation in the protein spot intensity was observed. The protein spots intensities were on average higher in S. aureus ST9 strain isolated from pigs than pig handlers. Variation in the spot positional correlation between the isolates from two different hosts was found to be less. From the comparative exoproteome, IsaA was found to be dominantly expressed in S. aureus, irrespective of their source. A comprehensive analysis of the exoproteome (pI 4-7) of S. aureus of similar or distinct genetic backgrounds (based on sequence type) isolated from healthy carriers (n = 6) and different clinical manifestations such as SSTIs (n = 6) and bacteremia (n =6) was performed. These included ST8, ST30, ST1963 and ST1964 from carriers,ST30, ST239, and ST1 from SSTIs and ST1, ST80, ST1179 and ST1899 from bactermia patients. There was considerable heterogeneity in the exoproteomes even of clonally closely related S. aureus isolates. Generally, spot patterns of S. aureus isolates within each group were more similar to each other than those of strains obtained from different groups. However, considering the pronounced overall heterogeneity in the exoproteomes of S. aureus, the identification of infection-related protein signatures will be challenging.